2018
DOI: 10.1016/j.actbio.2018.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt (II) ions and nanoparticles induce macrophage retention by ROS-mediated down-regulation of RhoA expression

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 60 publications
1
26
0
1
Order By: Relevance
“…The significant correlation of MRI off‐resonance frequency density with the necrosis grades shown in Table 4 is supportive of the proposed hypothesis on the clinical significance of Co over Cr ion concentrations in THA. This observation is also supported by recent pathological study findings by Xu et al, 31 which demonstrated that Co, rather than Cr, has a distinctive pathogenesis signature causing macrophage retention by restructuring the cytoskeleton and inhibiting cell migration via reactive oxygen species production that affects Rho family GTPase.…”
Section: Discussionsupporting
confidence: 81%
“…The significant correlation of MRI off‐resonance frequency density with the necrosis grades shown in Table 4 is supportive of the proposed hypothesis on the clinical significance of Co over Cr ion concentrations in THA. This observation is also supported by recent pathological study findings by Xu et al, 31 which demonstrated that Co, rather than Cr, has a distinctive pathogenesis signature causing macrophage retention by restructuring the cytoskeleton and inhibiting cell migration via reactive oxygen species production that affects Rho family GTPase.…”
Section: Discussionsupporting
confidence: 81%
“…Studies have shown that Co(II), Ni(II) and Cr(III) can significantly reduce cell vitality and cause pathological changes such as cell contraction, shedding, vacuole and swelling, apoptotic cells increased mostly in Co(II) exposure, and cell necrosis was predominant in Ni(II) exposure [53][54][55][56]. Co(II) can significantly reduce the movement ability of macrophages and inhibit cell migration by RhoA downregulation and cytoskeleton reorganization, which is still happened by the emergence of ROS [57]. Ni ions gradually accumulated in cells also affect the ability of bone morphogenetic protein (BMP-2) to induce alkaline phosphatase (ALP) formation [58,59].…”
Section: Different Metal Ions Can Induce Cell Damagementioning
confidence: 99%
“…radicals through a Fenton-like reaction and produce a large number of reactive oxygen species (ROS) [12]. Oxidative stress is found to be one of the key mechanisms of cobalt cytotoxicity [1,[13][14][15][16][17]. However, the molecular mechanism of oxidative stress-induced cell death of CoNPs remains unclear.…”
Section: Introductionmentioning
confidence: 99%